Utilization of Hydroxyapatite from Quail Eggshells as an Adsorbent for Lead Metal Ions Pb(II) - Alif, Matlal Fajri; Darajat, Syukri; Azizah, Siti (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Lead is a toxic metal known for its harmful effects, even in minor quantities, because it does not break down naturally and can therefore pollute ecosystems. This research involved the creation of hydroxyapatite using quail egg shell through a sol-gel method, which served as a medium for capturing Pb ions in a batch process by assessing different parameters. The created material was analyzed using X-Ray Diffraction (XRD) to confirm its crystal form, SEM (Scanning Electron Microscopy) to analyze its surface, FTIR (Fourier Transform Infrared Spectroscopy), and morphology to determine the functional units that were present. Sorption tests were performed under various scenarios, encompassing different pH levels, the initial Pb ion concentration, and time of contact, with the outcome evaluated through atomic absorption spectrophotometry (AAS). The results demonstrated that the optimal conditions for Pb ion uptake were observed at a concentration of 800 mg/L with 0.1 g of absorbent as well as a contact time of 60 minutes, achieving a lead ion removal rate of 71.48%. The sorption isotherm followed the Langmuir model, while the sorption kinetics fit the pseudo-order two model, indicating a monolayer sorption mechanism on a uniform surface. These outcomes suggest hydroxyapatite derived from quail eggshells is a promising eco-friendly material for treating wastewater containing heavy metal ions.